The compatibility of positive psychology and the Ludic strategy in foreign language education - Siek-Piskozub, Teresa (Glottodidactica, 2016)
The Ludic strategy, an approach to foreign language teaching (FLT), popularised by the present author since the 1990’s which acknowledges the value of a humanistic approach, yet also emphasises an emergence of positive feelings, while engaging in the ludic tasks for FLT purposes, is in line with the claims of positive psychology. For the analysis the most popular model of the well-being theory, Seligman’s PERMA model will be used. Referring to research in FLT on language competence, I will analyse the benefits of applying LS in the FL classroom, and by using the PERMA model I will show that LS can be treated as a useful tool for FLT congruent with the claims of positive psychology, and that the model can be used in planning FLT research.